Microbial volatile organic compounds: Antifungal mechanisms, applications, and challenges - Zhao, Xixi; Zhou, Jingyi; Tian, Ruofei; Liu, Yanlin (Frontiers in Microbiology, 2022)
The fungal decay of fresh fruits and vegetables annually generates substantial global economic losses. The utilization of conventional synthetic fungicides is damaging to the environment and human health. Recently, the biological control of post-harvest fruit and vegetable diseases via antagonistic microorganisms have become an attractive possible substitution for synthetic fungicides. Numerous studies have confirmed the potential of volatile organic compounds (VOCs) for post-harvest disease management. Moreover, VOC emission is a predominant antifungal mechanism of antagonistic microorganisms. As such, it is of great significance to discuss and explore the antifungal mechanisms of microbial VOCs for commercial application. This review summarizes the main sources of microbial VOCs in the post-harvest treatment and control of fruit and vegetable diseases. Recent advances in the elucidation of antifungal VOC mechanisms are emphasized, and the applications of VOCs produced from antagonistic microorganisms are described. Finally, the current prospects and challenges associated with microbial VOCs are considered.